High Response Photodetection by Applying the Optimized Photoreceptor Protein Modification on Graphene Based Field Effect Transistors - Tong, Jing; Zhang, Lei; Wang, Yi; Li, Tie (Frontiers in Materials, 2020)
In this work, we combined photoreceptor protein with graphene based field effect transistors to achieve a high responsivity photodetector. Three different aromatic hydrocarbons were used to functionalize graphene with carboxyl groups via π-π stacking interactions, and 1-pyrenebutyric acid exhibited the best result for photoreceptor protein immobilization. Besides, the modification procedure of photoreceptor protein was also optimized by using a novel protein stack way on the device. Unlike conventional self-assembly method, photoreceptor proteins were cross-linked before immobilized on graphene thin film and yielded a higher modification density. Finally, the photocurrent response was significantly enhanced from -1% to -9.62%. These results bring key opportunity for graphene field effect transistor based photodetection, and the surface functionalization method are expected to help achieve high sensing performance on protein-based biosensors.